A Novel Approach in Raman Temperature Sensing in Optical Fiber based on Broadband Incident Light - Renner, Esther; Härteis, Lisa-Sophie; Weiss, Nico; Schmauß, Bernhard (OSA Technical Digest, 2021)
We describe a new approach in Raman temperature sensing based on broadband incident light. The reported results show the proof of concept and thus form an important basis for future distributed temperature sensing systems.

Concept for Raman Distributed Temperature Sensing in Optical Fibers based on Standard C-Band Spectrometer - Renner, Esther; Härteis, Lisa-Sophie; Scheffter, Kilian; Schmauß, Bernhard (Optics InfoBase Conference Papers, 2022)
We propose a concept for Raman distributed temperature sensing based on L-band excitation and C-band Anti-Stokes detection. The concept is demonstrated by interrogation of 1500 m fiber with incoherent optical frequency domain reflectometry.
Created from Fastlane, Scopus look-up

Digitalized Optical Sensor Network for Intelligent Facility Monitoring - Renner, Esther; Härteis, Lisa-Sophie; Kaiser, Joachim; Villnow, Michael; Richter, Markus; Thiel, Torsten; Pohlkötter, Andreas; Schmauß, Bernhard (Photonics, 2024)
Due to their inherent advantages, optical fiber sensors (OFSs) can substantially contribute to the monitoring and performance enhancement of energy infrastructure. However, optical fiber sensor systems often are standalone solutions and do not connect to the main energy infrastructure control systems. In this paper, we propose a solution for the digitalization of an optical fiber sensor system realized by the Open Platform Communications Unified Architecture (OPC UA) protocol and the Internet of Things (IoT) platform Insights Hub. The optical fiber sensor system is based on bidirectional incoherent optical frequency domain reflectometry (biOFDR) and is used for the interrogation of fiber Bragg grating (FBG) arrays. To allow for an automated sensor identification and thus measurement procedure, an optical sensor identification marker based on a unique combination of fiber Bragg gratings (FBGs) is established. To demonstrate the abilities of the digitalized sensor network, a field test was performed in a power plant test facility of Siemens Energy. Temperature measurements of a packaged FBG sensor fiber were performed with a portable demonstrator, illustrating the system’s robustness and the comprehensive data processing stream from sensor value formation to the cloud. The realized network services promote sensor data quality, fusion, and modeling, expanding opportunities using digital twin technolog
Keywords: optical fiber sensing; fiber Bragg grating; sensor identification; digitalization; OPC UA; Internet of Things

Effective light coupling in reflective fiber optic distance sensors using a double-clad fiber - Werzinger, Stefan; Härteis, Lisa-Sophie; Köhler, Aaron; Engelbrecht, Rainer; Schmauß, Bernhard (International Conference on Optical Fiber Sensors (OFS), 2017)
Many fiber optic distance sensors use a reflective configuration, where a light beam is launched from an optical fiber, reflected from a target and coupled back into the fiber. While singlemode fibers (SMF) provide low-loss, high-performance components and a well-defined output beam, the coupling of the reflected light into the SMF is very sensitive to mechanical misalignments and scattering at the reflecting target. In this paper we use a double-clad fiber (DCF) and a DCF coupler to obtain an enhanced multimodal coupling of reflected light into the fiber. Increased power levels and robustness are achieved compared to a pure SMF configuration. © (2017) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use onl
lhft_intern.bib::Werzinger2017a

Exceeding Hardware Confined Bandwidth in Incoherent Optical Frequency Domain Reflectometry - Härteis, Lisa-Sophie; Renner, Esther; Schmauß, Bernhard (2022 IEEE Photonics Conference, IPC 2022 - Proceedings, 2022)
Bidirectional incoherent optical frequency domain reflectometry exhibits confined spatial resolution through the Mach-Zehnder Modulator's restricted bandwidth in backward direction. We propose hardware confined bandwidth exceedance by utilizing digital signal processing and therewith improve the spatial resolution by a factor of four.
CRIS-Team Scopus Importer:2024-12-16
Keywords: electrical bandwidth; fiber Bragg gratings; OFDR; signal processing; spatial resolution

Implementation of a Digital Shadow for Fiber Bragg Gratings - Renner, Esther; Härteis, Lisa-Sophie; Rittler, Andreas; Schmauß, Bernhard (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2021)
We propose a synthesis model for fiber Bragg gratings (FBGs) to monitor temperature measurement errors due to aging behavior. This approach might be called a Digital Shadow since we are able to monitor all essential parameters of the grating to perform error prediction and consequently compensation. The model is tested during accelerated aging experiments, which furthermore reveal the shift of the center wavelength because of thermal decay.
CRIS-Team Scopus Importer:2021-10-22

Interrogation von FBG Arrays in komplexen Sensornetzwerken mittels IOFDR - Härteis, Lisa-Sophie; Schmauß, Bernhard (ITG-Workshop KT31 (Modellierung und Simulation photonischer Komponenten und Systeme), 2020)

Quasi-distributed temperature sensing with large-scale draw tower gratings - Härteis, Lisa-Sophie; Renner, Esther; Scheffter, Kilian; Schmauß, Bernhard (Optics InfoBase Conference Papers, 2021)
Large-scale draw tower gratings (DTG) are interrogated using incoherent optical frequency domain reflectometry (iOFDR) w ith h omodyne f requency conversion. We successfully demonstrate quasi-distributed temperature sensing with a total number of N = 500 DTGs.
CRIS-Team Scopus Importer:2021-12-17

Time and Wavelength Division Multiplexing of Branched Fiber Bragg Grating Arrays - Härteis, Lisa-Sophie; Renner, Esther; Schmauß, Bernhard (2020)